Crime, Violence, At-Risk Youth, and Responsible Tourism in Latin America and the Caribbean - Cohan, Lorena (World Bank, Washington, DC, 2012)
The Latin America and Caribbean (LAC) region has one of the highest levels of crime and violence in the world. While the average world homicide rate is 11 homicides per 100,000 residents, the rate in the LAC region is 36 per 100,000 (WHO, 2003). Crime and violence are now recognized as serious economic and social problems with very high economic and social costs, especially in poor urban areas. By some estimates, the region loses up to 14 percent of its gross domestic product (GDP) to violence. Particularly worrisome is the fact that youth in the region (typically defined as 15-24 year-olds) and young men in particular are disproportionately involved in violence, as both victims and perpetrators. As a case in point, the LAC region has the world's highest homicide rate of men between the ages of 15 and 29 (69 per 100,000), with perpetrators of violent crimes most often being young men between the ages of 16 and 25. This note provides an overview of three sustainable tourism initiatives in the region that seek to link tourism related activities with social programs that by focusing on the most common types of risk factors help prevent youth from becoming engaged in at-risk behavior, including crime and violence. All three of these initiatives were highlighted at the 'learning event on sustainable and responsible tourism in LAC.' Although the initiatives described in this note have not yet undergone impact evaluations, they do provide promising ideas for future Bank operations that seek to link sustainable tourism and at-risk youth programs.